2020
DOI: 10.1186/s13002-020-0355-7
|View full text |Cite
|
Sign up to set email alerts
|

Monpa, memory, and change: an ethnobotanical study of plant use in Mêdog County, South-east Tibet, China

Abstract: Background: Due to their relative isolation, the previous studies of Monpa plant use were only conducted in north-east India. In October 2013, Mêdog County was no longer remote, thanks to completion of a highway into the county. This study of plant species used by the Monpa had three research objectives. These were (i) to identify and record local names and uses of plants in Mêdog County, (ii) to assess which of these were uses of endemic or near-endemic species within this part of the Indo-Burma biodiversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 66 publications
(34 reference statements)
2
28
0
Order By: Relevance
“…Most of previous studies in the region were about biodiversity, and just few studies involved the relationship between local people and biodiversity such as the local knowledge of plants [16]. In our preliminary Ethnobotanical studies of local people in the region, we found rich local knowledge of plants [19][20][21]. The functions of the plants in home gardens played important roles in the daily lives of local people.…”
Section: Introductionmentioning
confidence: 83%
“…Most of previous studies in the region were about biodiversity, and just few studies involved the relationship between local people and biodiversity such as the local knowledge of plants [16]. In our preliminary Ethnobotanical studies of local people in the region, we found rich local knowledge of plants [19][20][21]. The functions of the plants in home gardens played important roles in the daily lives of local people.…”
Section: Introductionmentioning
confidence: 83%
“…Most of previous studies in the region were about biodiversity, and just few studies involved the relationship between local people and biodiversity such as the local knowledge of plants [13]. In our preliminary Ethnobotanical studies of local people in the region, we found rich local knowledge of plants [16][17][18]. The functions of the plants in home gardens played important roles in the daily lives of local people.…”
Section: Introductionmentioning
confidence: 83%
“…S. heterophylla is also used by other indigenous tribes settle in Himalaya region. Our previous study showed that the species was consumed as fruit by Monpa in eastern Himalaya [47,48]. Besides, S. heterophylla is also used in local medicine.…”
Section: The Important Wepsmentioning
confidence: 99%